2010
DOI: 10.1007/s00417-010-1462-2
|View full text |Cite
|
Sign up to set email alerts
|

Goldmann applanation tonometry and dynamic contour tonometry in eyes with elevated intraocular pressure (IOP): comparison in the same eyes after subsequent medical normalization of IOP

Abstract: DCT-IOP, which is higher than GAT-IOP in normotensive eyes, is lower in eyes with GAT-IOP exceeding 30 mmHg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
3
0
1
Order By: Relevance
“…Further research in a large population is needed to determine the DCT IOP distribution curve with the corresponding statistical limits, as a benchmark for the clinical evaluation of DCT measurements independently of GAT. In addition it should be clarified, why the IOP differences between the two methods tend to diminish with increasing IOP 22,56. This tendency was also derived from the Bland–Altman plot of our data, but was not significant.…”
Section: Discussionmentioning
confidence: 48%
“…Further research in a large population is needed to determine the DCT IOP distribution curve with the corresponding statistical limits, as a benchmark for the clinical evaluation of DCT measurements independently of GAT. In addition it should be clarified, why the IOP differences between the two methods tend to diminish with increasing IOP 22,56. This tendency was also derived from the Bland–Altman plot of our data, but was not significant.…”
Section: Discussionmentioning
confidence: 48%
“…According to studies using human cadaver eyes, IOP values measured by DCT were significantly closer to the manometric reference pressure than the GAT measurements 17 . Previous studies have demonstrated an excellent agreement between GAT and DCT, although DCT readings tended to be generally higher in healthy eyes and glaucomatous eyes 4, 9, 10, 18. Conversely to RT, there are many studies investigating DCT measurements in keratoconic corneas.…”
Section: Discussionmentioning
confidence: 95%
“…DCT did not significantly correlate with CCT in our study. DCT has been proposed to measure IOP irrespective of the corneal thickness because DCT does not flatten the cornea, which allows the cornea to maintain its shape provoking minimal distortion during the measurement 4, 8, 9, 10, 16, 17, 18…”
Section: Discussionmentioning
confidence: 99%
“…GAT 38,7 ± 9,1 mmHg, p < 0,001) aufwies. Nach drucksenkender Therapie zeigten sich allerdings höhere Werte für die DCT im Vergleich zur GAT (DCT: 17,9 ± 3,1 mmHg vs. GAT 15,6 ± 2,7 mmHg, p < 0,001) [18]. Schwenteck et al konnten in einer Normalpopulation zeigen, dass die DCT die Kriterien des ISO-8612-Standards nicht erfüllte.…”
Section: Diskussion !unclassified